Isolation, culture and host colonization of Entrophospora schenckii (Glomales), an arbuscular mycorrhizal fungus - Fracchia, S. (2003)
Entrophospora schenckii was found for the first time in Argentina. Single-spore cultures were established to observe root colonization and developmental stages of spore production. The fungus produced vesicular-arbuscular mycorrhizae.